Efficacy of Resveratrol Supplementation on Glucose and Lipid Metabolism: A Meta-Analysis and Systematic Review - Zhou, Qian; Wang, Yanmei; Han, Xuke; Fu, Shunlian; Zhu, Chan; Chen, Qiu (Frontiers in Physiology, 2022)
Introduction Lipids are ubiquitous metabolites with diverse functions and it overload causes lipid redistribution among metabolic organs such as adipose, liver and muscle. And lipidomics has revealed that human morbidity be highly associated with altered lipid metabolism, especially, the complications from multiple diseases. Resveratrol is a phytoestrogen with antioxidant, can modulate the insulin resistance and lipid profile. It is essential for definite the efficacy of resveratrol supplementation on glucose and lipid metabolism. To evaluate the efficacy and safety of Resveratrol, a systematic review was performed. Methods and analysis We searched Pub Med, Cochrane Library, Web of Science databases and EMBASE from inception to April 2021 using relevant keywords and a comprehensive search for randomized controlled trials (RCTs) was performed. Pooled prevalence and its 95% confidence interval (95CI) were estimated using the inverse-variance weighting method. All related statistical analyses were performed using Rev Man V.5.3 software version 5.3 and STATA V.15 software. After data synthesis, the conclusions of the current meta-analysis demonstrated there are significant effects of resveratrol intake for WC, HemoglobinA1c (HbA1c), (TC), LDL-C and HDL-C reduction. These results suggest that resveratrol has a dramatic impact on regulating lipid and glucose metabolism, and the important clinical implications of resveratrol intake is mainly for the obese patients and diabetic patients.